Praktický příklad použití injektovaného systému kotvení etics a cenové porovnání - Nykodýmová, Veronika (Akademické nakladatelství CERM, 2017)
V České republice dochází ke zlepšování tepelně technických parametrů u obvodových stěn budov pomocí vnějšího tepelně izolačního kompozitního systému (dále jen ETICS) již o roku 1993. Od tohoto roku až do současnosti se požadavky na systém ETICS postupně zpřísňovaly a došlo i k tvorbě závazných norem a pokynů pro montáž tohoto systému. Je tedy důležité zamyslet se nad faktem, že budovy, zateplené např. před dvaceti lety dle platné legislativy, nyní náročným požadavkům ani zdaleka nevyhovují. Často je tedy možné se setkat s nedostatečnou tloušťkou izolantu, a to na již zateplených objektech (i 40–50 mm), a s výraznými poruchami stability systému, kdy hrozí i riziko zřícení původního zateplení. Nabízí se tedy otázka, jakým způsobem a „za kolik“ opravit či zdvojit dříve provedené zateplovací systémy ETICS na budovách, které jsou dnes z hlediska normativních požadavků již nevyhovující, či vykazují vady. Dá se předpokládat, že téma nekvalitně provedených ETICS se v blízké době značně dotkne i znalecké praxe a znalec bude ve svých posudcích řešit nejen otázku, z jakého důvodu došlo u konkrétního ETICS k poruchám a vadám dříve, než na konci životnosti systému, ale jeho úkolem bude např. i ocenění stavebních prací souvisejících s nápravou vadně provedeného ETICS.

In the Czech Republic, the improvement of thermal-technical parameters of the enclosing walls of buildings using the external thermal insulation composite systems (hereinafter ETICS) already in 1993. From this year, up to the present day with the system requirements ETICS gradually were tightened and there has been a creation of mandatory standards and guidelines for the installation of this system. It is therefore important to consider the fact that buildings insulated, e.g. twenty years ago, according to the applicable legislation, now far from the demanding requirements. Often it is possible to meet up with inadequate thickness of the insulating material on the already existing objects (40–50 mm), and with significant problems of stability of the system, where there is the risk of the collapse of the original insulation. Thus, the question of how, and “how much”, corrected or duplicate a previously made insulation systems ETICS on buildings that are today in terms of the normative requirements of the already inadequate or defects. It can be assumed that the topic of poorly made ETICS in the near future, greatly affect appraisal practice and the appraiser will be.
A Practical Example of the Using of the Injected System Anchoring Etics and Price Comparation
Keywords: In the Czech Republic, the improvement of thermal-technical parameters of the enclosing walls of buildings using the external thermal insulation composite systems (hereinafter ETICS) already in 1993. From this year, up to the present day with the system requirements ETICS gradually were tightened and there has been a creation of mandatory standards and guidelines for the installation of this system. It is therefore important to consider the fact that buildings insulated, e.g. twenty years ago, according to the applicable legislation, now far from the demanding requirements. Often it is possible to meet up with inadequate thickness of the insulating material on the already existing objects (40–50 mm), and with significant problems of stability of the system, where there is the risk of the collapse of the original insulation. Thus, the question of how, and “how much”, corrected or duplicate a previously made insulation systems ETICS on buildings that are today in terms of the normative requirements of the already inadequate or defects. It can be assumed that the topic of poorly made ETICS in the near future, greatly affect appraisal practice and the appraiser will be.; tepelná izolace; polystyren; injektovaný systém kotvení; zdvojení ETICS; cenové porovnání; porucha stability ETICS